Prostitution in medieval and early modern literature - Classen, Albrecht (Lexington Books, 2019)
Intro; Contents; Chapter One: Prostitution; Chapter Two: Modern Voices and Witnesses of Prostitution in Literature; Chapter Three: The Canoness Hrotsvit and the Prostitute; Chapter Four: Christine de Pizan's Advice to Prostitutes; Chapter Five: Prostitution in the Work of Late Medieval Poetry; Chapter Six: Prostitution in the Works by François Villon; Chapter Seven: The Prostitute as Protagonist; Chapter Eight: The Sojourn in a Brothel; Chapter Nine: The Prostitute and Prostitution in Late-Medieval and Early Modern German Song Poetry; Chapter Ten: Prostitutes in fabliaux, mæren, and novelli Chapter Eleven: Prostitutes in Sixteenth-Century Schwänke (Prose Jest Narratives)Epilogue; Bibliography; Index; About the Author Using an interdisciplinary approach and incorporating sources from across the entire European continent dating from the early Middle Ages to the sixteenth century, this book examines the phenomenon of prostitution in a variety of contexts and highlights the extent to which the institution mattered for both the higher and the lower classes
Includes bibliographical references and index
Keywords: Electronic books; Prostitution; Prostitutes in literature